2020
DOI: 10.7759/cureus.9118
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Extracorporeal Membrane Oxygenation in Patients With Hematologic Malignancies: A Literature Review

Abstract: Extracorporeal membrane oxygenation (ECMO) is used to provide respiratory and/or circulatory support for critically ill patients. In people suffering from hematologic malignancies (HMs), acute respiratory failure often necessitates intensive care. Whereas initial studies reported that these patients generally have poor outcomes, studies conducted within the last 10 years have shown that ECMO is quite beneficial for patients with HMs. This review showcases data from 2010 to 2019 demonstrating the utility of ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In a report by Wohlfarth et al among patients with hematological malignancy and acute respiratory failure, ECMO was successfully weaned in 10 out of 17 episodes (59%), and seven patients survived until discharge ( 24 ). A series of case reports have also suggested the potential role of ECMO as a bridge to curative chemotherapy in patients with hematological malignancies ( 25 ). For patients with autoimmune diseases, several studies have also reported that ECMO may serve as a bridge to immunomodulation in patients with pulmonary hemorrhage related to ANCA-associated vasculitis and systemic lupus erythematous ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a report by Wohlfarth et al among patients with hematological malignancy and acute respiratory failure, ECMO was successfully weaned in 10 out of 17 episodes (59%), and seven patients survived until discharge ( 24 ). A series of case reports have also suggested the potential role of ECMO as a bridge to curative chemotherapy in patients with hematological malignancies ( 25 ). For patients with autoimmune diseases, several studies have also reported that ECMO may serve as a bridge to immunomodulation in patients with pulmonary hemorrhage related to ANCA-associated vasculitis and systemic lupus erythematous ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In cases of hematological malignancies, early initiation of chemotherapy after a definitive diagnosis is critical to improving survival. An ECMO might be useful as a bridge to chemotherapy in patients with airway emergencies to increase the survival rate for such patients [ 4 ]; however, remission-induction chemotherapy causes neutropenia and an immunocompromised state, placing patients at risk of severe infections, such as ventilator-associated pneumonia. In such situations, ES may shorten the intensive care period [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 365‐day mortality due to cancer was highest in the other diagnoses group (36.7%), suggesting that many cancer patients received ECMO support during cancer treatment. Cancer often causes unpredictable cardiac or respiratory failure during treatment, which requires temporary ECMO support 25,26 . In particular, there are reports that ECMO support may be a useful treatment option for patients with lung cancer or hematologic malignancies 25–27 .…”
Section: Discussionmentioning
confidence: 99%